Environment and social justice an international perspective - Taylor, Dorceta E. (Bingley, U.K. : Emerald, 2010)
This volume examines domestic and international environmental issues from an environmental justice perspective. The book is a compilation of original research articles and is divided into six parts. Articles in Part I focus on urban environmental issues and sustainability including Central Park's influence on historical and contemporary models of funding public parks, London's community-based efforts to deliver affordable fresh food to the poor and the relationship between sustainable living, green consumption and social justice concerns in an ecovillage in New York. Part II concentrates on water resources and the hazards of toxic fish consumption. Part III features food security, agriculture and land loss. Energy and the theme of land and resource loss in host communities is the focus in Part IV. It discusses the poverty that is pervasive in communities hosting extractive oil and gas installations and the industry and attitudes towards it in rural Trinidad and Nigeria. Part V employs spatial analyses techniques to examine siting and toxic releases and Part VI examines diversity and environmental attitudes and presents findings of national studies and environmental conflicts.
Introduction / Dorceta E. Taylor -- Equity, influence, and access : Central Park's role in historical and contemporary urban park financing / Dorceta E. Taylor -- Movements, neighborhood change, and the media : newspaper coverage of anti-gentrification activity in the San Francisco Bay Area : 1995-2005 / June Gin, Dorceta E. Taylor -- Food security and sustainability : community food initiatives in London / Shumaisa Khan -- Sustainable living and community building in Ecovillage at Ithaca : the challenges of incorporating social justice concerns into the practices of an ecological cohousing community / Tendai Chitewere, Dorceta E. Taylor -- The domestic and international dimensions of methylmercury contamination in Tuna : an analysis of the efficacy of the fish advisory standards of two federal agencies / Beth Pallo, Marlene Barken -- Fish consumption and environmental justice in the great lakes : the influence of fish advisories on risk perception, knowledge, and behavior of white and minority anglers / Brenda J. Nordenstam, Sarah Darkwa -- From the green revolution to the gene revolution in India : understanding the risks and benefits of genetically modified crops / Asmita Bhardwaj -- Heritage tourism : a mechanism to facilitate the preservation of black family farms / Stephanie Freeman, Dorceta E. Taylor -- Environmental perceptions and action : villagers' response to oil and gas drilling in the wetlands of rural Trinidad / A. Karen Baptiste, Brenda J. Nordenstam -- Oil and gas industry in Nigeria : the paradox of the black gold / Joseph Effiong -- Building community capacity? : mapping the scope and impacts of EPA's environmental justice small grants program / Shalini P. Vajjhala -- Race, gender, and faculty diversity in environmental disciplines / Dorceta E. Taylor -- Why can't they work together? : a framework for understanding conflict and collaboration in two environmental disputes in Southeast Michigan / Sarah Lashley, Dorceta E. Taylor -- Environmentalism and Islam : a study of Muslim women in the United States / Jumana Vasi -- Concluding remarks / Dorceta E. Taylor.
Keywords: Political Science -- General; Social Science -- General; Political science & theory; The environment; Environmental justice; Social justice